Retracted: MyoD-dependent regulation of NF-κB activity couples cell-cycle withdrawal to myogenic differentiation - Parker, Maura H; von Maltzahn, Julia; Bakkar, Nadine; Al-Joubori, Ban; Ishibashi, Jeff; Guttridge, Denis; Rudnicki, Michael A (Université d'Ottawa | University of Ottawa, 2012)
Abstract Background Mice lacking MyoD exhibit delayed skeletal muscle regeneration and markedly enhanced numbers of satellite cells. Myoblasts isolated from MyoD -/- myoblasts proliferate more rapidly than wild type myoblasts, display a dramatic delay in differentiation, and continue to incorporate BrdU after serum withdrawal. Methods Primary myoblasts isolated from wild type and MyoD -/- mutant mice were examined by microarray analysis and further characterized by cell and molecular experiments in cell culture. Results We found that NF-κB, a key regulator of cell-cycle withdrawal and differentiation, aberrantly maintains nuclear localization and transcriptional activity in MyoD -/- myoblasts. As a result, expression of cyclin D is maintained during serum withdrawal, inhibiting expression of muscle-specific genes and progression through the differentiation program. Sustained nuclear localization of cyclin E, and a concomitant increase in cdk2 activity maintains S-phase entry in MyoD -/- myoblasts even in the absence of mitogens. Importantly, this deficit was rescued by forced expression of IκBαSR, a non-degradable mutant of IκBα, indicating that inhibition of NF-κB is sufficient to induce terminal myogenic differentiation in the absence of MyoD. Conclusion MyoD-induced cytoplasmic relocalization of NF-κB is an essential step in linking cell-cycle withdrawal to the terminal differentiation of skeletal myoblasts. These results provide important insight into the unique functions of MyoD in regulating the switch from progenitor proliferation to terminal differentiation.